The neural bases of cognitive control - Cohen, Jonathan (Henry Stewart Talks, 2012)
Model of the Stroop task, Guided activation theory, How representations develop, Control representations, Attractors and interference, Gated attractor network, Dopamine as a gating mechanism, Timing of phasic DA signal, The "homunculus" problem, Adaptive updating of control, AX-CPT: cue, delay and target, Timing of gating signal as function of training, Canonical task, fMRI: localization of context representations, EEG: timing of gating signal, TMS: disruption of gating event, fMRI identification of updating-related VTA signal